Desenvolvimento de um código computacional bidimensional em linguagem fortran para a solução do problema da cavidade - Vieira, Haustin Stelmastchuk (2014)
This work consists on the development and validation of a two-dimensional computational code in language Fortran for solution of the lid-driven cavity problem. Defined the physical problem, this code is characterized by the second order Central Differencing Scheme (CDS) for spatial discretization and the Euler scheme for time advancement. In section 2 the governing equations and the mathematical models for the flow inside the square cavity are show. Section 3 shows the methodology which was applied to numerically solve this problem. Simulation results are presented in the section 4. Finally a good convergence with benchmarks results in the literature validates the developed numerical tool.